Electroluminescence of Giant Stretchability - Yang, Can Hui; Chen, Baohong; Zhou, Jinxiong; Chen, Yong Mei; Suo, Zhigang (Advanced materials (Weinheim), 2016)
A new type of electroluminescent device achieves giant stretchability by integrating electronic and ionic components. The device uses phosphor powders as electroluminescent materials, and hydrogels as stretchable and transparent ionic conductors. Subject to cyclic voltage, the phosphor powders luminesce, but the ionic conductors do not electrolyze. The device produces constant luminance when stretched up to an area strain of 1500%.